Photobiomodulation therapy in the treatment of Stevens-Johnson syndrome oral lesions: case report - Amaral Rocha, Breno (2020)
Introduction: Stevens-Johnson Syndrome is a rare reaction manifested by a rash that evolves into extensive epidermal dislocation. In most cases there are painful oral mucosal lesions that can reduce nutrient intake and make oral hygiene difficult. Photobiomodulation therapy can play an important antalgic role in modulating inflammation and healing these lesions. Objective: To report a clinical case in which Stevens-Johnson Syndrome oral lesions were treated with the aid of photobiomodulation therapy. Case report: A 17-year-old female patient diagnosed with Stevens-Johnson syndrome presented with lip edema, oral ulcers, fever, and severe odynophagia, tolerating only a liquid diet. She experienced reduced food intake, no efficient oral communication, and an interruption of oral hygiene due to intense pain. Photobiomodulation therapy was requested to treat the oral lesions. Conclusion: Photobiomodulation therapy helped reduce pain, favored oral food intake, and reduced lesion healing time.